Tres piezas de música carranguera, para piano a cuatro manos (2020)
This research and creation work proposes an interpretation from the piano perspective, of the music that was born in the geographical area from which my father: land to which I feel tied by ties of love and blood. Also searched reflect at a sociocultural level, about the importance of carranguera music in the consolidation of boyacense cultural identity and how this music was, has been and will be a benchmark of the power that music and artists in general have, as cohesive of a society and as guardians of the collective memory of communities and of the cultural heritage. It was proposed then, to try to interweave the sounds of some jewels of this peasant music, with the technical and timbre possibilities that a traditional piano and create from this a memory in principle familiar, of our proud peasant roots, that in a world like today, take on an immaterial value that with all conviction I think should be preserved. Although the work of Jorge Velosa and the other carranga musicians who have accompanied in his creations, has been a source of entertainment, dances and laughter, among the peasant population to which it was initially addressed; beyond. ³LRV caUUaJXeURV of RaTXLUi' initiated a cultural revolution in the Cundiboyacense region, which claimed, the pride in being a peasant, historically a victim of dispossession and abandonment by a State indolent towards its most humble populations. They vindicated the pride of belonging to this region, full of material and cultural wealth, thanks to its people and their customs that sadly, for decades they were despised and undervalued.Three representative pieces will be adapted in this project in the tradition of the music by Jorge Velosa, to the language of the traditional piano, doing everything possible to preserve his carranguero sound as a small tribute to him and to all the musicians of carranga throughout these years. Although, when beginning the approach to the work of Jorge Velosa y los Carrangueros, it was found that his music today is widely known in the central region of the country, he It is also evidence that with the passing of recent years, new popular music has been stealing prominence among the younger population, since the music industry with the help from the media, in which they also have a part; drive tendencies far removed from the cultural roots of the regions globally, making the new generations leave on an increasingly relegated plane, the traditions of which we come from I believe in the importance of preserving cultural identity as a intangible heritage that from the academy must be promoted, conserved and also develop: with this project, it is intended, even if it is, to contribute a small grain of sand to this important task. The reader will find a brief approach to what has been written and done to date. moment from the academy, which involves carranguera music as thematic axis, as well as as the process by which these adaptations were chosen and executed finally achieved; including a formal musical analysis of each piece, a transcription of the essential melodies, harmonies and rhythms in which it is played develop them, as well as the process by which they are will develop the project ³Three pieces of carranguero music for four hands piano´. Which is finally the fruit that was born from this work.